A water-gas shift reaction catalyst and its preparation method and application
By using NaNbO3-CeO2 composite oxide support and Pt catalyst, the problem of insufficient activity and poor stability of water gas transformation catalyst at high temperatures is solved, and a water gas transformation reaction with high activity and good stability is achieved, which is suitable for high aerial speed and rapid start and stop. fuel cell system.
Patent Information
- Application Number
- CN202111466756.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-03
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-12-03
AI Technical Summary
The existing water-gas transformation catalysts are insufficient in activity at high temperatures, have poor stability in long-term operation and start-stop, and lack new carriers with high activity and stability.
The catalyst was prepared by hydrothermal method and impregnation method by using NaNbO3-CeO2 composite oxide as a support and combined with Pt as an active metal to improve the activity and stability of the catalyst.
It achieves a water-gas transformation reaction with high activity, selectivity and stability, adapts to high aerial speed operation and the rapid start and repeated start-stop environment of fuel cell systems, and overcomes the limitations of traditional catalysts.
Smart Images

Figure CN116212867B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a water-gas shift reaction catalyst and a preparation method and application thereof. Background Art
[0002] With the development of economy, the demand for energy is getting higher and higher, and the impact of energy consumption on the environment is increasing. People are eager to seek an alternative energy source or a cleaner and more efficient way to utilize fossil energy. Hydrogen energy is currently recognized as a clean energy source and is considered to be the most promising secondary energy source. With the development of hydrogen energy economy, hydrogen fuel cells have become an important new energy application platform. Whether using fossil fuels or ethanol and methanol as raw materials, the reforming process produces a large amount of CO while producing H2. CO has a strong poisoning effect on fuel cell electrocatalysts, so fuel cells have strict restrictions on the CO content in hydrogen raw materials, which is generally less than 10ppm. In order to prevent CO in hydrogen fuel cells from poisoning fuel cell catalysts, the water-gas shift reaction is required to purify the hydrogen fuel. Therefore, the water-gas shift catalyst plays a very important role in fuel cells and is the key to the commercialization of hydrogen-carrying fuel cells.
[0003] Industrial water-gas shift reaction is usually carried out in a fixed bed reactor equipped with Fe3O4-Cr2O3 or Cu / ZnO / Al2O3 catalyst. Fe3O4-Cr2O3 is used for high-temperature water-gas shift reaction, with an operating temperature of 350-400°C, to achieve a faster conversion of CO, but due to the limitation of thermodynamic equilibrium, the CO concentration cannot be reduced to a very low level; Cu / ZnO / Al2O3 is used for low-temperature water-gas shift reaction, with an operating temperature of 200-250°C, to further reduce the CO concentration.
[0004] Since traditional water-gas shift catalysts have many limitations in fuel cell applications, the development of new water-gas shift catalysts for fuel cell hydrogen production systems has attracted great attention. The new water-gas shift catalysts must have high activity and structural stability in air and during cyclic operation. At present, precious metal (such as Pt, Au, etc.) catalysts supported by various oxide carriers (such as CeO2, ZrO2, TiO2, etc.) are the most studied non-traditional water-gas shift catalysts. The advantages of this type of catalyst are: (1) high mechanical strength, (2) not very sensitive to poisons such as Cl and S.
[0005] KG Azzam et al. reported a Pt / TiO2 water-gas shift catalyst (Applied Catalysis A: General, 2008, 338, 66–71). Although the catalyst has good initial activity, its stability is poor. After 22 hours of reaction at 300°C, the activity decreased by 35%. Xinsheng Liu et al. reported a Pt / CeO2 catalyst (Applied Catalysis B: Environmental, 2005, 56, 69–75). The catalyst has good stability in steady-state operation, but its activity decreases rapidly after start-stop cycles under feed gas. Wolfgang Ruettinger et al. reported a Pt / ZrO2-CeO2 catalyst (Applied Catalysis B: Environmental, 2006, 65, 135–141). The catalyst has the problem of decreased reaction stability both in steady-state operation and after start-stop cycles, and is not suitable for practical application.
[0006] Chinese patent CN108144608A discloses a platinum-based water-gas shift catalyst and a preparation method. Specifically, a cerium source solution is added dropwise to a precipitant solution, and the solution is continuously stirred and kept at a pH value of about 10, and then filtered, washed, dried, and calcined to obtain a CeO2 carrier. The platinum source and the cobalt source are loaded on the CeO2 carrier by a co-impregnation method, with a Pt content of 2wt% and a Co content of 0.1-1wt%. The catalyst prepared by this method performs a water-gas shift reaction in a typical reformed gas and has high activity and stability. Under the same precious metal loading, the addition of Co significantly improves the water-gas shift reaction activity and stability of Pt / CeO2.
[0007] Chinese patent CN105983427A discloses a Pt / apatite water-gas shift reaction catalyst, which is specifically prepared by a coprecipitation method for hydroxyapatite and halogen-substituted apatite, and platinum is introduced by an impregnation method. The platinum loading in the catalyst is 0.3%-5% of the total mass of the catalyst. The catalyst prepared by this method is subjected to a water-gas shift reaction in a typical reformed gas, and at the same precious metal loading, it exhibits a higher activity than the precious metal loaded on a reducible rare earth oxide carrier (CeO2).
[0008] Chinese patent CN1674328 discloses a carbon monoxide water gas shift reaction catalyst for a fuel cell hydrogen source process, a preparation method and an application. The catalyst composition is a noble metal / CeO2-transition metal oxide, the noble metal loading range is 0.1-3% of the total weight of the catalyst, and the molar ratio of the transition metal oxide to CeO2 ranges from 1:1-9. The catalyst has good water gas shift reaction performance.
[0009] Chinese patent CN1000429814C discloses a Pt / CeO2-ZrO2 integral water-gas shift catalyst. -1 At an air velocity of 250 °C, the CO conversion rate is only about 30%; Wang Shudong et al. (Journal of Fuel Chemistry, 2008, 36, 625-630) reported a Re / Pt / Ce 0.8 Zr 0.2 O2 integral catalyst, the catalyst in 10000h -1 At an air velocity of 1.5 ℃, the CO conversion rate is only about 70% at 250℃.
[0010] In summary, although the performance of Pt-based conversion catalysts has been greatly improved after years of research, there are still the following shortcomings: 1. The catalyst activity is insufficient, especially the activity below 300°C needs to be improved; 2. The catalyst has insufficient stability in long-term operation and start-stop; 3. It is still necessary to find a new type of carrier that makes the catalyst more active and stable. Summary of the invention
[0011] Based on the above research status, the present invention proposes a carbon monoxide water gas shift catalyst and its preparation method and application. The catalyst provided by the present invention uses NaNbO3-CeO2 composite oxide as a carrier and Pt as an active metal. The catalyst has the advantages of high activity, high selectivity and good stability in the carbon monoxide water gas shift reaction.
[0012] To achieve the above object, the technical solution of the present invention is as follows:
[0013] The first aspect of the present invention provides a water-gas shift reaction catalyst, wherein the catalyst composition is Pt / NaNbO3-CeO2. The active component of the catalyst is Pt, and the Pt content is 0.5% to 10% of the total mass of the catalyst, preferably 0.8 to 8wt%, and more preferably 1 to 5wt%. The carrier of the catalyst is a NaNbO3-CeO2 composite oxide, and the NaNbO3 content in the carrier is 5% to 50% of the total mass of the NaNbO3-CeO2 composite oxide, preferably 8 to 40wt%, and more preferably 10 to 30wt%.
[0014] A second aspect of the present invention provides a method for preparing a Pt / NaNbO3-CeO2 catalyst, the preparation method comprising the following steps:
[0015] (1) Preparation of NaNbO3-CeO2 composite oxide carrier: Dissolve cerium nitrate in deionized water, then add Nb2O5 to the cerium nitrate solution and stir evenly; then add sodium hydroxide solution to the Nb2O5-cerium nitrate suspension and stir vigorously for 1 to 60 minutes. Transfer the obtained suspension to a hydrothermal reactor and perform a hydrothermal reaction at 100 to 220°C for 0.5 to 24 hours. After the hydrothermal reaction is completed, cool the hydrothermal reactor to room temperature, filter the obtained solid, and wash it with deionized water until it is neutral. Finally, dry the obtained solid at 60 to 120°C for 2 to 24 hours, and then heat it from room temperature to the drying temperature to 300 to 600°C for calcination at a heating rate of 1 to 20°C / min for 0.5 to 10 hours to obtain a NaNbO3-CeO2 composite oxide carrier. The concentration of the cerium nitrate solution is 0.05 to 1 mol / L, and the concentration of the sodium hydroxide solution is 1 to 30 mol / L.
[0016] (2) Catalyst preparation: The NaNbO3-CeO2 composite oxide solid powder obtained in step (1) is used as a carrier, and a soluble salt of the active metal platinum is loaded onto the carrier by impregnation, and dried at 60-120°C for 4-24 hours; the dried product is placed in an air atmosphere and / or an inert atmosphere, and the temperature is raised from room temperature to the drying temperature at a rate of 1-20°C / min to 300-600°C, and calcined for 0.5-10 hours to obtain a Pt / NaNbO3-CeO2 catalyst.
[0017] The concentration of the cerium nitrate solution in the step (1) is preferably 0.1-0.8 mol / L, more preferably 0.15-0.5 mol / L; the concentration of the sodium hydroxide solution is preferably 2-25 mol / L, more preferably 5-20 mol / L; the hydrothermal reaction temperature is preferably 140-190°C, more preferably 150-180°C; the hydrothermal reaction time is preferably 1-10 h, more preferably 2-8 h; the drying temperature of the obtained solid is preferably 70-110°C, more preferably 80-100°C; the drying time is preferably 2-20 h, more preferably 4-15 h; the temperature is programmed from room temperature to the drying temperature to the calcination temperature, the heating rate is preferably 3-10°C / min, more preferably 5-8°C / min; the calcination temperature is preferably 350-550°C, more preferably 400-500°C; the calcination time is preferably 1-8 h, more preferably 2-4 h.
[0018] In the step (2), the soluble salt of platinum is one or more of chloroplatinic acid, platinum chloride, platinum nitrate, tetraamine platinum dichloride, tetraamine platinum nitrate, tetraamine platinum acetate or acetylacetonate platinum; the catalyst drying temperature is preferably 70-110°C, more preferably 80-100°C; the drying time is preferably 2-20h, more preferably 4-15h; the temperature is programmed from room temperature to the drying temperature to the calcination temperature, and the heating rate is preferably 3-10°C / min, more preferably 5-8°C / min; the calcination temperature is preferably 350-550°C, more preferably 400-500°C; the calcination time is preferably 1-8h, more preferably 2-4h.
[0019] The third aspect of the present invention provides an application of a Pt / NaNbO3-CeO2 catalyst, wherein the catalyst is used for a water-gas shift reaction of carbon monoxide. The catalyst does not need to be pre-reduced when used in a water-gas shift reaction. The conditions for the water-gas shift reaction are: water and CO are essential components in the reaction gas, and the molar ratio of water to CO is (2.0-12):1, preferably (2.5-10):1, and more preferably (3-8):1; the reaction gas does not contain or contains non-essential components, and the non-essential components are one or more of N2, CO2, H2, Ar, and He, and the molar fraction of the non-essential components in the reaction gas is 0-90%; the space velocity of the reaction raw materials through the catalyst bed is 5000-500000 ml·h -1 ·g -1 催化剂 , preferably 10000~400000ml·h -1 ·g -1 催化剂 , more preferably 20000 to 300000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1 to 4 MPa, preferably 0.1 to 2 MPa, and more preferably 0.1 to 1 MPa; the reaction temperature is 200 to 550°C, preferably 225 to 450°C, and more preferably 250 to 450°C.
[0020] The reaction evaluation device process for verifying the technical solution of the present invention is as follows Figure 1 As shown. The raw gas ① is metered by the flow meter ② and then enters the preheater ⑤. The water ③ is quantitatively transported into the preheater ⑤ through the metering pump ④. The mixed material is preheated to 100-400℃ in the preheater ⑤. The preheated material enters the reactor ⑦ set in the heating area of the reactor ⑥. The constant temperature area of the reactor ⑦ is provided with a catalyst bed ⑧. After the reaction, the material is separated into gas phase products and condensed water through the condenser ⑨. The condensed water is released by the stop valve ⑩ at an appropriate time, and the gas product is discharged through the back pressure valve ⑩. After it drops to normal pressure, it passes through the gas flow meter After metering, empty the pipe. There is a sampling branch on the top to supply the gas chromatograph Sampling and analysis.
[0021] Compared with conventional high temperature shift and low temperature shift catalysts, the present invention has the following advantages:
[0022] (1) The Pt / NaNbO3-CeO2 catalyst provided by the present invention is prepared by a hydrothermal method and an impregnation method, and has the advantages of being simple, mature and highly repeatable.
[0023] (2) In the Pt / NaNbO3-CeO2 catalyst provided by the present invention, during the hydrothermal treatment, the formation of NaNbO3 is conducive to the generation of oxygen defects, which greatly increases the CeO2 surface Ce in the composite oxide. 3+ concentration, thereby improving the water-gas shift reaction activity of the catalyst.
[0024] (3) The Pt / NaNbO3-CeO2 catalyst provided by the present invention has the advantages of high activity, high selectivity, good stability and resistance to high space velocity operation in the water-gas shift reaction.
[0025] (4) The Pt / NaNbO3-CeO2 catalyst provided by the present invention does not require reduction operation before use and is not afraid of air oxidation. It can adapt to the application environment of rapid startup and repeated start and stop of fuel cell systems, overcomes many limitations of traditional conversion catalysts under non-steady-state conditions, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the CO water-gas shift reaction evaluation device flow chart;
[0027] ①CO raw gas, ②flow meter, ③water, ④metering pump, ⑤preheater, ⑥reaction furnace, ⑦reactor, ⑧catalyst bed, ⑨condenser, ⑩stop valve, Back pressure valve, Gas flow meter, Gas chromatograph, Vent the line.
[0028] Figure 2 The XRD diagrams of the catalyst supports prepared in Examples 1 to 4, Comparative Example 1 and Comparative Example 2 are shown.
[0029] Figure 3 The XRD diagrams of the catalysts prepared in Examples 1 to 4, Comparative Example 1 and Comparative Example 2 are shown.
[0030] Figure 4 These are the water-gas shift reaction test data obtained in Examples 12 to 15.
[0031] Figure 5 The water-gas shift reaction test data obtained in Examples 12 and 16 to 19 are
[0032] Figure 6 These are the water-gas shift reaction test data obtained in Example 12 and Example 20.
[0033] Figure 7 The water-gas shift reaction test data of the catalyst obtained in Example 21 at different space velocities.
[0034] Figure 8 This is the catalyst stability test data obtained in Example 22.
[0035] Fig. 9 This is the catalyst oxygen shock stability test data obtained in Example 23.
[0036] Fig.10 These are the water-gas shift reaction test data obtained in Example 12 and Comparative Examples 3 to 6. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments.
[0038] Example 1
[0039] (1) Weigh 5.05g of cerium nitrate hexahydrate and dissolve it in 30mL of deionized water. Then weigh 0.6307g of Nb2O5 and add it to the cerium nitrate solution and stir vigorously to make it uniform. Then add 40ml of the prepared 5mol / L sodium hydroxide solution to the Nb2O5-cerium nitrate suspension and stir vigorously for 30 minutes. The obtained suspension is transferred to a 100ml hydrothermal kettle and subjected to hydrothermal reaction at 150°C for 2h. After the hydrothermal reaction is completed, the hydrothermal kettle is cooled to room temperature, the obtained solid is filtered, and washed with deionized water until it is neutral. The obtained solid is dried at 80°C for 4h, and finally the obtained solid is heated from room temperature to the drying temperature to 400°C at a rate of 5°C / min and calcined for 2h to obtain a 28wt% NaNbO3-CeO2 composite oxide carrier. The XRD pattern is shown in Figure 2 The results show that the XRD pattern mainly shows diffraction peaks of NaNbO3 and CeO2, indicating that the obtained substance is a NaNbO3-CeO2 composite oxide.
[0040] (2) Weigh 1.0 g of the 28 wt% NaNbO3-CeO2 composite oxide solid powder obtained in step (1), weigh 0.0265 g of chloroplatinic acid and dissolve it in 1 ml of deionized water to obtain an impregnation solution, then add the impregnation solution to the NaNbO3-CeO2 composite oxide carrier, stir evenly and dry at 80°C for 2 h; place the dried product in an air atmosphere and heat it from room temperature to the drying temperature to 400°C at a rate of 5°C / min, and calcine it for 2 h. The obtained catalyst is represented by 1Pt / 28wt% NaNbO3-CeO2, and the XRD pattern is shown in FIG. Figure 3 The results show that there is no diffraction peak of active metal platinum in the XRD pattern, indicating that the active metal is evenly distributed on the composite oxide support.
[0041] Embodiment 2:
[0042] The process of Example 1 was repeated, except that the amount of Nb2O5 added in step (1) was 0.0854 g, and the catalyst finally obtained was 1Pt / 5wt% NaNbO3-CeO2. The XRD pattern of the carrier is shown in FIG. Figure 2 , the catalyst XRD pattern is shown in Figure 3 From the XRD graph of the carrier, it can be seen that the diffraction peak is mainly CeO2, and there is no diffraction peak of NaNbO3, indicating that NaNbO3 is uniformly dispersed in CeO2; there is no diffraction peak of active metal platinum in the XRD graph of the catalyst, indicating that the active metal is uniformly distributed on the composite oxide carrier.
[0043] Embodiment 3:
[0044] The process of Example 1 was repeated, except that the amount of Nb2O5 added in step (1) was 0.2640 g. The catalyst finally obtained was 1Pt / 14wt% NaNbO3-CeO2. The XRD pattern of the carrier is shown in FIG. Figure 2 , the catalyst XRD pattern is shown in Figure 3 From the XRD graph of the carrier, it can be seen that the diffraction peak is mainly CeO2, and there is no diffraction peak of NaNbO3, indicating that NaNbO3 is uniformly dispersed in CeO2; there is no diffraction peak of active metal platinum in the XRD graph of the catalyst, indicating that the active metal is uniformly distributed on the composite oxide carrier.
[0045] Embodiment 4:
[0046] The process of Example 1 was repeated, except that the amount of Nb2O5 added in step (1) was 1.6219 g. The catalyst finally obtained was 1Pt / 50wt% NaNbO3-CeO2. The XRD pattern of the carrier is shown in FIG. Figure 2 , the catalyst XRD pattern is shown in Figure 3From the XRD graph of the carrier, it can be seen that the diffraction peaks are mainly NaNbO3 and CeO2, and the intensity of the diffraction peak of NaNbO3 is significantly stronger than that of 28wt% NaNbO3-CeO2; no diffraction peak of active metal platinum is found in the XRD graph of the catalyst, indicating that the active metal is evenly distributed on the composite oxide carrier.
[0047] Embodiment 5:
[0048] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added in step (2) was 0.0530 g, and the final catalyst obtained was 2Pt / 28wt% NaNbO3-CeO2.
[0049] Embodiment 6:
[0050] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added in step (2) was 0.1325 g, and the final catalyst obtained was 5Pt / 28wt% NaNbO3-CeO2.
[0051] Embodiment 7:
[0052] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added in step (2) was 0.2650 g, and the final catalyst obtained was 10Pt / 28wt% NaNbO3-CeO2.
[0053] Embodiment 8:
[0054] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added in step (2) was 0.0133 g, and the final catalyst obtained was 0.5Pt / 28wt%NaNbO3-CeO2.
[0055] Embodiment 9:
[0056] The process of Example 1 was repeated, except that the hydrothermal reaction temperature in step (1) was 160°C, the hydrothermal reaction time was 18 h, and the final catalyst obtained was 1Pt / 28wt%NaNbO3-CeO2-160°C-18h.
[0057] Embodiment 10:
[0058] The process of Example 1 was repeated, except that in step (1), the concentration of sodium hydroxide was 10 mol / L, the hydrothermal reaction temperature was 100°C, the hydrothermal reaction time was 24 h, the drying time temperature was 60°C, the drying time was 24 h, the roasting temperature rise rate was 1°C / min, the roasting temperature was 300°C, and the roasting time was 10 h. In step (2), the drying time temperature was 60°C, the drying time was 24 h, the roasting temperature rise rate was 1°C / min, the roasting temperature was 300°C, and the roasting time was 10 h. The catalyst finally obtained was 1Pt / 28wt%NaNbO3-CeO2-100°C-24h.
[0059] Embodiment 11:
[0060] The process of Example 1 was repeated, except that in step (1), the concentration of sodium hydroxide was 30 mol / L, the hydrothermal reaction temperature was 220°C, the hydrothermal reaction time was 0.5 h, the drying time temperature was 120°C, the drying time was 2 h, the roasting temperature rise rate was 20°C / min, the roasting temperature was 600°C, and the roasting time was 0.5 h. In step (2), the drying time temperature was 120°C, the drying time was 2 h, the roasting temperature rise rate was 20°C / min, the roasting temperature was 600°C, and the roasting time was 0.5 h. The catalyst finally obtained was 1Pt / 28wt%NaNbO3-CeO2-220°C-0.5h.
[0061] Embodiment 12:
[0062] CO Water Gas Shift Reaction Evaluation:
[0063] The 1Pt / 28wt% NaNbO3-CeO2 catalyst obtained in Example 1 was tableted and granulated, and then 0.2g (40-60 mesh) was placed Figure 1 The water-gas shift reaction was evaluated in the micro fixed-bed reactor shown in FIG. The reaction feed gas composition was 40% H2 / 15% CO / 13% CO2 / 32% Ar (volume ratio), the water to CO molar ratio was 3, and the mixed gas feed flow rate was 230 ml min -1 , converted to the feed mass space velocity (WHSV) of about 100000 ml h -1 ·g -1 催化剂 , the reaction pressure was 0.1 MPa, the reaction temperatures were 200°C, 250°C, 275°C, 300°C, 325°C, 350°C, 400°C, and 550°C, and the reaction time was 30 min at each temperature. The specific results are shown in Figure 4 .
[0064] Embodiment 13:
[0065] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / 5wt% NaNbO3-CeO2 prepared in Example 2. The specific results are shown in Figure 4 .
[0066] Embodiment 14:
[0067] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / 14wt% NaNbO3-CeO2 prepared in Example 3. The specific results are shown in Figure 4 .
[0068] Embodiment 15:
[0069] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / 50wt% NaNbO3-CeO2 prepared in Example 4. The specific results are shown in Figure 4 .
[0070] Embodiment 16:
[0071] The process of Example 12 was repeated, except that the catalyst used was the catalyst 2Pt / 28wt% NaNbO3-CeO2 prepared in Example 5. The specific results are shown in Figure 5 .
[0072] Embodiment 17:
[0073] The process of Example 12 was repeated, except that the catalyst used was the catalyst 5Pt / 28wt% NaNbO3-CeO2 prepared in Example 6. The specific results are shown in Figure 5 .
[0074] Embodiment 18:
[0075] Example 12 was repeated except that the catalyst used was the catalyst 10Pt / 28wt% NaNbO3-CeO2 prepared in Example 7. The specific results are shown in Figure 5 .
[0076] Embodiment 19:
[0077] The process of Example 12 was repeated, except that the catalyst used was the catalyst 0.5Pt / 28wt% NaNbO3-CeO2 prepared in Example 8. The specific results are shown in Figure 5 .
[0078] Embodiment 20:
[0079] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / 28wt% NaNbO3-CeO2 prepared in Example 9-160℃-18h. The specific results are shown in Figure 6 .
[0080] Embodiment 21:
[0081] The process of Example 12 was repeated, except that the reaction temperature was fixed at 400°C, and the feed flow rate of the reaction mixture was adjusted to be 5000 ml·h-1 and 5000 ml·h-2, respectively. -1 ·g -1 催化剂 、100000ml·h -1 ·g -1 催化剂 、200000ml·h -1 ·g -1 催化剂 、300000ml·h -1 ·g -1 催化剂 、500000ml·h -1 ·g -1 催化剂 The activity of 1Pt / 28wt%NaNbO3-CeO2 catalyst at different space velocities at 400℃ was investigated. The specific results are shown in Figure 7 .
[0082] Embodiment 22:
[0083] The process of Example 12 was repeated except that the reaction temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 The results of sampling and analysis were performed every 1 hour. The stability of the 1Pt / 28wt% NaNbO3-CeO2 catalyst was investigated for 100 hours. The specific results are shown in Figure 8 .
[0084] Embodiment 23:
[0085] The process of Example 12 was repeated except that the reaction temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 After 30 minutes of reaction, the sample was collected and analyzed. Then the reaction was stopped, the feed gas was switched to air, the reactor temperature was kept at 400°C, and the activity was evaluated again after 30 minutes. This process was repeated 10 times to examine the oxygen impact resistance of the catalyst. The specific results are shown in Fig. 9 .
[0086] Embodiment 24:
[0087] The process of Example 12 was repeated, except that the molar ratio of water to CO was adjusted to 2:1 and the pressure was adjusted to 4 MPa.
[0088] Embodiment 25:
[0089] The process of Example 12 was repeated, except that the molar ratio of water to CO was adjusted to 12:1.
[0090] Comparative Example 1
[0091] The process of Example 1 was repeated, except that Nb2O5 was not added in step (1). The catalyst obtained was 1Pt / CeO2. The XRD pattern of the CeO2 carrier was shown in FIG. Figure 2 The XRD pattern of catalyst 1Pt / CeO2 is shown in Figure 3 The results show that the diffraction peak in the carrier XRD pattern is the CeO2 diffraction peak, and no active metal platinum diffraction peak is found in the catalyst XRD pattern, indicating that platinum is uniformly dispersed on the carrier CeO2.
[0092] Comparative Example 2
[0093] The process of Example 1 was repeated, except that cerium nitrate was not added in step (1). The catalyst finally obtained was 1Pt / NaNbO3. The XRD pattern of the carrier NaNbO3 is shown in FIG. Figure 2 The XRD pattern of catalyst 1Pt / NaNbO3 is shown in Figure 3 The results show that the diffraction peak in the carrier XRD pattern is the NaNbO3 diffraction peak, and no active metal platinum diffraction peak is found in the catalyst XRD pattern, indicating that platinum is uniformly dispersed on the carrier NaNbO3.
[0094] Comparative Example 3
[0095] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / CeO2 prepared in Comparative Example 1. The specific results are shown in Fig.10 .
[0096] Comparative Example 4
[0097] The process of Example 12 was repeated, except that the catalyst used was the catalyst 1Pt / NaNbO3 prepared in Comparative Example 1. The specific results are shown in Fig.10 .
[0098] Comparative Example 5
[0099] The process of Example 12 was repeated, except that the catalyst used was Fe3O4-Cr2O3 industrial high temperature shift catalyst. Fig.10 .
[0100] Comparative Example 6
[0101] The process of Example 12 was repeated, except that the catalyst used was Cu / ZnO / Al2O3 industrial low temperature shift catalyst. Fig.10 .
[0102] The application test results show that the Pt / NaNbO3-CeO2 catalyst provided by the present invention has excellent catalytic performance for water-gas shift reaction: (1) 1Pt / 28wt%NaNbO3-CeO2 catalyst is in a simulated atmosphere of 40%H2 / 15%CO / 13%CO2 / 32%Ar, with a water to CO molar ratio of 3:1 and a space velocity of 100000ml·h -1 ·g -1 催化剂 Under the same conditions, the CO conversion rate at 300°C is close to the equilibrium conversion rate, and the activity is much higher than that of Pt / CeO2 water-gas shift catalyst. (2) 1Pt / 28wt%NaNbO3-CeO2 catalyst has good stability. In the simulated atmosphere of 40%H2 / 15%CO / 13%CO2 / 32%Ar, the molar ratio of water to CO is 3:1, the reaction temperature is 400°C, and the space velocity is 200000ml·h -1 ·g -1 催化剂 Under the same conditions, the CO conversion rate was always maintained above 75% within 100 hours, close to the equilibrium conversion rate. (3) The 1Pt / 28wt% NaNbO3-CeO2 catalyst has good performance at high space velocity. In the simulated atmosphere of 40% H2 / 15% CO / 13% CO2 / 32% Ar, the molar ratio of water to CO was 3:1, and the space velocity was as high as 500000 ml·h -1 ·g -1 催化剂 Under the same conditions, the CO conversion rate can still exceed 70% at 400℃, indicating that the catalyst is suitable for high space velocity operation. (4) Fig. 9 It can be seen that the 1Pt / 28wt% NaNbO3-CeO2 catalyst has excellent oxygen shock resistance and is suitable for the application environment of repeated start-stop of fuel cell systems. (5) Fig.10 It can be seen that the activity of 1Pt / 28wt% NaNbO3-CeO2 is much higher than that of the traditional Fe3O4-Cr2O3 high-temperature shift and Cu / ZnO / Al2O3 low-temperature shift catalysts, and is also much higher than that of the Pt / CeO2 catalyst.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes. Any modification, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A water-gas shift reaction catalyst, characterized in that: The catalyst composition is Pt / NaNbO3-CeO2; the active component of the catalyst is Pt, and the Pt content is 0.5% to 10% of the total mass of the catalyst; the carrier of the catalyst is NaNbO3-CeO2 composite oxide, and the NaNbO3 content in the carrier is 5% to 50% of the total mass of the NaNbO3-CeO2 composite oxide.
2. The water-gas shift reaction catalyst according to claim 1, characterized in that: The content of Pt, an active component of the catalyst, is 0.8-8wt%; the content of NaNbO3 in the carrier of the catalyst is 8-40wt%.
3. The water-gas shift reaction catalyst according to claim 1, characterized in that: The content of Pt, an active component of the catalyst, is 1-5wt%; the content of NaNbO3 in the carrier of the catalyst is 10-30wt%.
4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that The following steps are involved: (1) Preparation of NaNbO3-CeO2 composite oxide carrier: dissolve cerium nitrate in water, then add Nb2O5 to the cerium nitrate solution and stir evenly; then add sodium hydroxide solution to the Nb2O5-cerium nitrate suspension and stir for 1-60 minutes; transfer the obtained suspension to a hydrothermal reactor and perform a hydrothermal reaction at 100-220 °C for 0.5-24 h; after the hydrothermal reaction, cool the hydrothermal reactor to room temperature, filter the obtained solid, and wash it with deionized water until it is neutral; finally, dry the obtained solid at 60-120 °C for 2-24 h; program the temperature from room temperature to the drying temperature to 300-600 °C at a rate of 1-20 °C / min, and calcine for 0.5-10 h to obtain a NaNbO3-CeO2 composite oxide carrier; the concentration of the cerium nitrate solution is 0.05-1 mol / L, and the concentration of the sodium hydroxide solution is 1-30 mol / L; (2) Catalyst preparation: A soluble salt of active metal platinum is loaded onto the NaNbO3-CeO2 composite oxide carrier obtained in step (1) by impregnation, and dried at 60-120°C for 4-24 h; the dried product is placed in an air atmosphere and / or an inert atmosphere, and the temperature is raised from room temperature to the drying temperature to 300-600°C at a rate of 1-20°C / min, and calcined for 0.5-10 h to obtain a Pt / NaNbO3-CeO2 catalyst.
5. The method for preparing the catalyst according to claim 4, characterized in that: The concentration of the cerium nitrate solution in step (1) is 0.1-0.8 mol / L; the concentration of the sodium hydroxide solution is 2-25 mol / L; the sodium hydroxide solution is added to the Nb2O5-cerium nitrate suspension and stirred for 5-50 minutes; the hydrothermal reaction temperature is 140-190°C; the hydrothermal reaction time is 1-10 h; the drying temperature is 70-110°C, and the drying time is 2-20 h; the temperature is programmed from room temperature to the drying temperature to the roasting temperature, the heating rate is 3-10°C / min, the roasting temperature is 350-550°C, and the roasting time is 1-8 h; In the step (2), the soluble salt of platinum is one or more of chloroplatinic acid, platinum chloride, platinum nitrate, tetraamine platinum dichloride, tetraamine platinum nitrate, tetraamine platinum acetate or platinum acetylacetonate; the drying temperature is 70-110°C, and the drying time is 2-20 h; the temperature is programmed from room temperature to the drying temperature to the roasting temperature, the heating rate is 3-10°C / min, the roasting temperature is 350-550°C, and the roasting time is 1-8 h.
6. The method for preparing the catalyst according to claim 4, characterized in that: The concentration of the cerium nitrate solution in step (1) is 0.15-0.5 mol / L; the concentration of the sodium hydroxide solution is 5-20 mol / L; the sodium hydroxide solution is added to the Nb2O5-cerium nitrate suspension and the stirring time is 15-40 minutes; the hydrothermal reaction temperature is 150-180°C; the hydrothermal reaction time is 2-8 h; the drying temperature is 80-100°C, and the drying time is 4-15 h; the temperature is programmed from room temperature to the drying temperature to the roasting temperature, the heating rate is 5-8°C / min, the roasting temperature is 400-500°C, and the roasting time is 2-4 h; The drying temperature in step (2) is 80-100°C; the drying time is 4-15h; the temperature is raised from room temperature to the drying temperature to the calcination temperature at a heating rate of 5-8°C / min; the calcination temperature is 400-500°C; and the calcination time is 2-4h.
7. Use of the catalyst according to any one of claims 1 to 3, characterized in that: The catalyst is used for water gas shift reaction.
8. The use according to claim 7, characterized in that: The water-gas shift reaction conditions suitable for the catalyst are as follows: the reaction temperature is 200-550°C, water and CO are essential components in the reaction gas, and the molar ratio of water to CO is (2-12):1; the reaction gas does not contain or contains non-essential components, and the non-essential components are one or more of N2, CO2, H2, Ar, and He, and the molar fraction of the non-essential components in the reaction gas is 0-90%; the space velocity of the reaction raw materials passing through the catalyst bed is 5000-500000ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~4 MPa.
9. The use according to claim 8, characterized in that: The molar ratio of water to CO is (2.5-10):1; the reaction temperature is 225-500°C; the space velocity of the reaction raw materials passing through the catalyst bed is 10000-400000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~2 MPa.
10. The use according to claim 8, characterized in that: The molar ratio of water to CO is (3-8):1; the reaction temperature is 250-450°C; the space velocity of the reaction raw materials passing through the catalyst bed is 20000-300000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~1 MPa; The catalyst does not need to be reduced before catalyzing the reaction.
